Voluntary and evoked behavioral correlates in inflammatory pain conditions under different social housing conditions. (July 2016) - Pitzer, Claudia; Kuner, Rohini; Tappe-Theodor, Anke
Abstract : Abstract: Most preclinical pain models rely on short-duration stimulus-evoked hind paw measurements even though chronic pain is usually a day and night experience. Pain is a debilitating condition that influences the sociability and the ability for voluntary tasks, but the relevant behavioral readouts for these aspects are mostly underrepresented in the literature. Moreover, we lack standardization in most behavioral paradigms. Important aspects are herewith the combination and duration of particular behavioral tasks and the effects of social environment. We aimed at thoroughly investigating stimulus-evoked and voluntary behavioral parameters in the Complete Freund's Adjuvant model of unilateral hind paw inflammation in male mice. Moreover, we analyzed the impact of different social housing conditions. We used a portfolio of classical response measurements, detailed gait analysis, using 2 different measuring systems (Dynamic weight bearing and CatWalk), as well as observer-independent voluntary wheel running and homecage monitoring in a longitudinal time frame. The impact of grouped or isolated housing was investigated in all behavioral paradigms. We observed that unilateral hind paw inflammation provoked changes in several behaviors. Among these were wheel running activity and different homecage activity parameters. Stimulus-evoked hypersensitivity lasted much longer than gait abnormalities and decreased voluntary wheel running activity. Similar effects were monitored in both social housing conditions. This is the first longitudinal study providing detailed insights into various voluntary behavioral parameters related to pain in a unilateral inflammatory model. Stimulus-evoked behavioral changes lasted longer than changes in voluntary behavioral parameters, and the social environment hardly affects these changes.